If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3=-(r-17)
We move all terms to the left:
3-(-(r-17))=0
We calculate terms in parentheses: -(-(r-17)), so:We get rid of parentheses
-(r-17)
We get rid of parentheses
-r+17
We add all the numbers together, and all the variables
-1r+17
Back to the equation:
-(-1r+17)
1r-17+3=0
We add all the numbers together, and all the variables
r-14=0
We move all terms containing r to the left, all other terms to the right
r=14
| 0.65*x=8.25 | | 4(3x+2=5(3x-2) | | p+22=821 | | 4(3x+2=5(3x-2 | | r−150=20 | | s+130=690 | | 6x+7=13x-13 | | 956=f+944 | | v+626=787 | | w+367=691 | | r+221=355 | | 8x+27=32 | | 3x-5/21+x=3x+5/3+1 | | X^2-14x-11=11 | | Y=-120x+600 | | 2{3w+8}=40 | | (15)(2/3x+10)=(15)(×/5+36/5) | | c(19-c)=2(6c+2)+3c | | 6-0.3x=1 | | 15=k/27 | | 4x-x^2+5=0 | | 5•2-x•5=5 | | 551=19q | | 27n=945 | | p/29=26 | | 6=3Xw | | $16.25-b=$10.15 | | 9x=+23= | | -v+4v-12=-2 | | 11*n=312 | | 5b=500 | | 5(w-8)-7w=-38 |